Evaluation of Mineral Trioxide Aggregate and Biodentine as Direct Pulp-capping Agents in Human Teeth: An Ex-Vivo Study - Agrawal, Navin; Singh, Vimmi; Shrestha, Ashish; Jaisani, Mehul; Maharjan, Iccha Kumar; Jain, Neetu (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Biodentine (Tricalcium Silicate based) is a modern bioactive cement that is comparable to the broadly utilized mineral trioxide aggregate (MTA). It has dentin-like mechanical properties, which can be considered appropriate material for diseased dentin-pulp complex recovery such as direct pulp capping. The present study was to compare the reaction of the pulp-dentin complex in human teeth after direct pulp capping with use of MTA and Biodentine.Objective: To assess the histomorphologic response of human dental pulps on direct pulp capping with MTA and Biodentine.Methods: Pulps of 34 maxillary permanent intact human third molars planned for extraction were mechanically exposed with sterile rotary round bur and allotted to one of the two exploratory groups, MTA or Biodentine. After four weeks, the teeth were extracted, stained with hematoxylin- eosin, and categorized by employing a preset histologic scoring framework. The histopathologic evaluations scored data were recorded and statically analyzed using SPSS where Mann-Whitney U test was used and p